Histological and immunohistochemical study of the protective effect of virgin coconut oil on cyclophosphamide-induced immunotoxicity of the spleen and peyer’s patches - AlJoufi, Fakhria A. AlJoufi; M. Senin, Mu’izuddin; I.Matloub, Gheed; A. Wahab Alsiadi, Wasan; Al-Ani, Imad M.; Mustafa Mahmoud, Mohammed Imad Al-Deen; S.Ahmed, Fakhri; Najm Abed, Shaymaa (2022)
Introduction: Virgin coconut oil (VCO) is an edible oil extracted from the meat of mature coconuts. It is also known for its health and therapeutic benefits, mainly attributed to its polyphenols and medium-chain fatty acid contents The immunomodulatory effects of VCO have not been extensively investigated. The aim of the present study was to investigate the effects of VCO on cyclophosphamide (CY)-induced immunotoxicity of peripheral lymphoid tissues. Methods: Forty Wistar rats were divided into five groups of eight rats each. Group 1 served as the normal control, while the other groups were all given 10 mg/kg of CY orally once daily for 4 weeks. Group 2 received CY served as the negative control. Group 3 rats were treated with levamisole (LMS) for 6 weeks, while Groups 4A and 4B were given VCO at 10 mL/kg and 15 mL/kg, respectively, for 6 weeks. The spleen and ileum sections were subjected to routine histological examination and immunohistochemical evaluation for T and B lymphocytes. Results: Histologically, the spleen and Peyer’s patches (PPs) of the ileum exhibited a significant reduction in the lymphoid cellularity following daily administration of 10 mg/kg CY for 4 weeks.